From Gold to Gaze: The Gendered Lens of Body Shaming in Online Media Coverage of Female Athletes - Nisrina, Rumaysha Gikha; Abrori, Raja Bintang (JURNAL SOSIAL HUMANIORA (JSH), 2024)
This study examines the construction of gender identity in online media coverage, focusing on the issue of body shaming directed at female athletes. The case of Indonesian weightlifter Nurul Akmal, who experienced body shaming after her participation in the 2020 Tokyo Olympics, is analysed using Alan McKee’s text analysis method, a descriptive qualitative approach, and a constructivist paradigm. News articles from eight prominent Indonesian online media outlets — CNNIndonesia.com, Kompas.com, Tempo.co, Detik.com, Republika.co.id, Liputan6.com, and Okezone.com — were selected as the primary data sources. The findings reveal that online media frequently frame negative commentary on female athletes' physical appearance as innocuous humour or mere jest. Furthermore, the portrayal of female athletes as passive or powerless reinforces their subordinate status within the patriarchal structure, limiting their ability to resist or challenge such derogatory narratives. This media construction not only perpetuates gender stereotypes but also undermines efforts to promote gender equality within the realm of sports. The study highlights the need for more critical and gender-sensitive reporting practices to counteract these harmful representations.